PEMANFAATAN DIGITAL MARKETING MELALUI SEMINAR STRATEGI SUKSES UMKM UNTUK MENINGKATKAN EKONOMI KELUARGA BAGI MASYARAKAT PESISIR PULO PANJANG BANTEN - Furtasan Ali Yusuf; Laksmi Evasufi Widi Fajari; Jaka Wijaya Kusuma; Hadi Kurniawanto; Syamsul Hidayat (LPPM Universitas Bina Bangsa, 2024)
This service activity aims to optimize the use of digital marketing through seminars on successful MSME strategies to improve the family economy for the coastal communities of Panjang Island, Banten. The total respondents involved in this survey were 20 MSME owners salting and boiling anchovies, banana chips, dola-dola dodol seaweed and seaweed cultivation. In this service activity, there are several stages of implementation including: (1) survey; (2) measure prior knowledge; (3) digital marketing assistance; and (4) evaluation. In addition, this activity also includes MSME mentoring activities in the form of continuous support. Results of the series of activities: (1) survey: Long Island coastal communities have great potential to develop their MSME businesses through digital marketing; (2) measuring prior knowledge to confirm survey findings, with the majority of seminar participants having a limited understanding of digital marketing; (3) mentoring activities involving seminars on digital marketing success strategies succeeded in providing in-depth insights to participants; and (4) the evaluation results of the seminar activities showed a significant increase in participants' understanding of digital marketing. Overall, this service activity proves that training and mentoring in digital marketing can provide tangible benefits for the coastal communities of Panjang Island